2004
DOI: 10.1073/pnas.0307565101
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated regulation of the TRPM7 channel through its endogenous protein kinase domain

Abstract: TRPM7 is a ubiquitously expressed and constitutively active divalent cation-selective ion channel, whose basal activity is regulated by intracellular levels of Mg 2؉ and Mg⅐ATP. We have investigated receptor-mediated mechanisms that may actively regulate TRPM7 activity. We here report that TRPM7 currents are suppressed by intracellular GTP␥S, suggesting the involvement of heterotrimeric G proteins. TRPM7 currents are also inhibited by stimulating endogenous muscarinic receptors, which is mediated by Gi because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
159
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(163 citation statements)
references
References 16 publications
2
159
1
1
Order By: Relevance
“…Another potential problem is the fact that the cells under investigation can have endogenous receptors that are activated in parallel with the overexpressed receptors, which is the case for muscarinic receptors, as some of them couple to PLC (M1, M3, M5) whereas others couple to Gi (M2, M4). Takezawa et al (2004) demonstrated that the muscarinic receptor-mediated inhibition of TRPM7 in HEK-293 cells by endogenous muscarinic receptors likely occurs via Gi-coupled pathways, since the effect was suppressed by pertussis toxin. They further demonstrated that TRPM7 currents are upregulated by isoproterenol (a beta receptor agonist that couples to Gs) or by perfusing cells with elevated cAMP.…”
Section: Regulation By Receptor Stimulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Another potential problem is the fact that the cells under investigation can have endogenous receptors that are activated in parallel with the overexpressed receptors, which is the case for muscarinic receptors, as some of them couple to PLC (M1, M3, M5) whereas others couple to Gi (M2, M4). Takezawa et al (2004) demonstrated that the muscarinic receptor-mediated inhibition of TRPM7 in HEK-293 cells by endogenous muscarinic receptors likely occurs via Gi-coupled pathways, since the effect was suppressed by pertussis toxin. They further demonstrated that TRPM7 currents are upregulated by isoproterenol (a beta receptor agonist that couples to Gs) or by perfusing cells with elevated cAMP.…”
Section: Regulation By Receptor Stimulationmentioning
confidence: 99%
“…Two conflicting reports have proposed regulatory mechanisms of TRPM7 by phosphatidylinositol bisphosphate (PIP 2 ) (Runnels et al 2002) and by cyclic AMP (cAMP) signaling (Takezawa et al 2004). Clapham and colleagues (2002) suggested that receptormediated PIP 2 is required to maintain TRPM7 activity, and its breakdown by receptormediated stimulation of phospholipase C (PLC) is responsible for the inhibition TRPM7 they observed when stimulating cells with agonists that couple to PLC.…”
Section: Regulation By Receptor Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Runnels et al phosphatidylinositol 4,5-biphosphate (PIP 2 ), the endogenous substrate of PLC, is required for TRPM7 channel activity and receptor-mediated activation of PLC decreases TRPM7 activity due to local hydrolysis of PIP 2 (Runnels et al 2002). On the contrary, Takezawa et al demonstrated that TRPM7, heterologously expressed in HEK293 cells, abolished activation of PLCβ via muscarinic and thrombin receptors coupled to G q proteins (Takezawa et al 2004). Moreover, TRPM7 channel activity was found to be positively modulated by receptors coupled to the G s /cAMP/ PKA signaling cascade.…”
Section: Trpm6 and Trpm7 Channel Subunits And Their Complexesmentioning
confidence: 99%